Model Host-Vector Penyebaran Virus Zika - Nadia Wulandari; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2020)
Abstract— Zika is a disease caused by the bite of an infected Aedes mosquitoes, especially the Aedes aegypti mosquitoes. Besides being transmitted by mosquito bites, zika can also be transmitted by human sexual contact. The purpose is to determine the spread of zika virus through two populations and determine the paraeters that affect the distribution that are sensitive or affect the dynamic system. This research is a basic research, using descriptive methods. This method is done by analyzing theories related to the problem. Based on the results of the sensitivity analysis, it was found that the parameter affecting the basic reproductive value was the rate of mosquito bites and lifespan of vector. If the mosquito bite rate and the lifespan of the mosquito increase, then the basic reproductive value will also increase so that the zika virus will become epidemic. Keywords— Host-Vector Model, Zika, Sexual Transmission, Vector Transmission.